2014
DOI: 10.1007/s11894-014-0392-2
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacologic Treatment of Short Bowel Syndrome: New Tricks and Novel Agents

Abstract: Short bowel syndrome (SBS) is a manifestation of massive resection of the intestines resulting in severe fluid, electrolyte, and vitamin/mineral deficiencies. Diet and parenteral nutrition play a large role in the management of SBS; however, pharmacologic options are becoming more readily available. These pharmacologic agents focus on reducing secretions and stimulating intestinal adaptation. The choice of medication is highly dependent on the patient's symptoms, remaining anatomy, and risk versus benefit prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 68 publications
0
15
0
2
Order By: Relevance
“…Loperamide is added to reduce gastrointestinal transit time through the reduction of circular and longitudinal muscle activity and to diminish gastric acid, biliary, and pancreatic secretions, thus reducing the fluid volume in the intestinal lumen. 22 At the time of restoring bowel continuity, the child then is more likely to have slower motility and therefore less perineal rash. In infants, high-output stomas are problematic because of the recurrent episodes of dehydration, electrolyte disturbance (particularly sodium loss), and failure to thrive, which might require repeated hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Loperamide is added to reduce gastrointestinal transit time through the reduction of circular and longitudinal muscle activity and to diminish gastric acid, biliary, and pancreatic secretions, thus reducing the fluid volume in the intestinal lumen. 22 At the time of restoring bowel continuity, the child then is more likely to have slower motility and therefore less perineal rash. In infants, high-output stomas are problematic because of the recurrent episodes of dehydration, electrolyte disturbance (particularly sodium loss), and failure to thrive, which might require repeated hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…Also proton-pump inhibitors seem to be more effective than H2-blockers in reducing intestinal output, but only when associated with antidiarrheals/antimotility agents when the dose is maximized. 22,23 If at the time of the planned pull through and/or ileostomy closure the consistency and volume of the ileostomy output do not improve, the surgery should be delayed to optimize the medical management of the hypermotility (►Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loperamide is often the first antimotility agent employed because of its relatively benign composition in comparison with diphenoxylate‐atropine (Lomotil), codeine, and tincture of opium. Although loperamide is an intestinal opioid receptor antagonist, it does not cross the blood‐brain barrier (BBB), thereby avoiding the risk of central nervous system (CNS) side effects 77,78 . In the case of high‐output ECFs, reports have found that a dose <12–24 mg/day is unlikely to be effective secondary to rapid transit of the medication 78 .…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
“…Short bowel syndrome (SBS) is a highly disabling malabsorptive syndrome characterized by inability to maintain protein energy, fluid, electrolyte, and micronutrient balance in the body due to loss of intestinal absorptive capacity from congenital defect or extensive small bowel resection in the setting of diseases such as Crohn's disease, ischemic bowel disease, pseudomyxoma peritonei, and cancer 1 – 3 . One of the most common clinical presentations is chronic diarrhea associated with weight loss, fatigue, edema, cramps, and dehydration 4 .…”
mentioning
confidence: 99%